The influence of career panels on student perceptions, attitudes, and intentions toward the information systems profession. (5th December 2021) - Merhout, Jeffrey W.; Benamati, John 'Skip'; Rajkumar, T.M.
ABSTRACT: Exposure to role models has been recommended as a way to attract and retain students in Information Systems (IS) programs. One way to accomplish this exposure in IS classrooms is with career panels of alumni professionals who offer a realistic perspective of various IS‐related roles and can frankly answer questions from students. For this study, we developed a comprehensive survey instrument based on published literature in order to examine the perceptions and attitudes of business students pre‐ and post‐ exposure to career panels and to validate that career panels indeed positively influence student perceptions and attitudes about IS. Female role models have also been espoused as a way to mitigate negative stereotypes, such as the IS field being a masculine domain or that a desirable work‐life balance is difficult to achieve. Our experimental design varied the gender mix of professionals between all‐male, all‐female, and mixed panels. We found that perceptions affect attitudes, and attitudes, in turn, influence intention to study IS. We also found that these role models positively influence perceptions of IS and that mixed panels influence perceptions more than all‐female and all‐male panels. In addition, we found that female students do not respond differently than male students to all‐female panels.